Aplicação de técnicas SPWM na segmentação dos polos da máquina síncrona de ímãs permanentes para redução na ondulação do torque - Andrade Júnior, Khristian Marques de (2020)
In the present work, six methods are proposed considering the application of PWM techniques in the pole segmentation of permanent magnet synchronous machines in order to reduce the value of the torque ripple. Such methods reduce this ripple by eliminating the back-emf low-order harmonics and reducing the amplitude of the cogging torque. The PWM techniques considered here are the unipolar sinusoidal, bipolar, trapezoidal and sinusoidal with harmonic injection. A finite element analysis of the designed machines, under no load and under load conditions, is carried out in order to validate the presented methods. Method 1 presents the best results when the amplitude modulation index was kept constant and with unit value, guaranteeing a reduction in the cogging torque of 78.54%, however also reducing the electromagnetic torque by 17.87%. The major disadvantage of Methods 2, 5 and 6 is the presence of low order harmonics in their back-emf. The effect of using fractional-pitch winding is evaluated when these methods are considered to surpass the mentioned problem, however it is observed that, contrary to what is desired, the the torque ripple increases, while its average value reduces. Furthermore, the elimination of segments with width of less than 5◦ results, in general, in an increase of the back-emf harmonics and a behavior of the cogging torque without an apparent trivial pattern. Finally, an optimization process is carried out for Methods 1, 5 and 6, as these present the best results, to determine the optimal values of the amplitude and frequency modulation indices that guarantee a reduction in the cogging torque and mitigate the depreciation in the machine torque. In this scenario, Method 6 has the best results, reducing the torque ripple by about 88.02%, and increasing the fundamental density of the air gap flux by 4.55% in relation to that one of the reference machine.